Grain boundary sliding in chromia thermally grown oxide. (December 2015) - Guerain, M.; Goudeau, P.; Grosseau-Poussard, J.L.
Graphical abstract: Abstract: Residual macrostresses in chromia thermal oxide films which develop on a Ni–30Cr alloy have been investigated at room temperature thanks to Raman spectroscopy and X-ray diffraction. Combined with atomic force microscopy on the oxidised surface which gives morphological features at the chromia grain scale, stress release processes in the ceramic films are studied. It is evidenced that grain boundary sliding is activated as a companion mechanism of diffusion-creep. Such processes are sensitive to the oxide microstructure and the cooling conditions.